The effect of delayed umbilical cord clamping on cord blood gas analysis in vaginal and caesarean‐delivered term newborns without fetal distress: a prospective observational study. (17th December 2019) - Giovannini, N; Crippa, BL; Denaro, E; Raffaeli, G; Cortesi, V; Consonni, D; Cetera, GE; Parazzini, F; Ferrazzi, E; Mosca, F; Ghirardello, S
Abstract : Objective: To determine variations in cord blood gas (CBG) parameters after 3‐minute delayed cord clamping (DCC) in vaginal deliveries (VDs) and caesarean deliveries (CDs) at term without fetal distress. Design: Prospective observational study. Setting: University hospital. Sample: CBG from 97 VDs and 124 CDs without fetal distress. Methods: Comparison of paired arterial–venous CBG parameters drawn at birth from the unclamped cord and after 3‐minutes DCC for VDs and CDs. Main outcome measures: Base excess, bicarbonate, haematocrit and haemoglobin from both arterial and venous cord blood, lactate, neonatal outcomes, partial pressure of oxygen (pO2 ), partial pressure of carbon dioxide (pCO2 ), pH, and postpartum haemorrhage. Results: Arterial cord blood pH, bicarbonate ( HCO 3 -, mmol/l), and base excess (BE, mmol/l) decreased significantly after 3‐minute DCC both in VDs (pH = 7.23 versus 7.27; P < 0.001; HCO 3 - = 23.3 versus 24.3; P = 0.004; BE = −5.1 versus −2.9; P < 0.001) and CDs (pH = 7.28 versus 7.34; P < 0.001; HCO 3 - = 26.2 versus 27.2; P < 0.001; BE = −1.5 versus 0.7; P < 0.001). After 3‐minute DCC, pCO2 increased in CDs only (57 versus 51; P < 0.001), whereas lactate increased more in CDs compared with VDs (lactate, +1.1 [0.9, 1.45] versus +0.5 [−0.65, 2.35]; P = 0.01). Postpartum maternal haemorrhage, neonatal maximum bilirubin concentration, and need for phototherapy were similar between the two groups. Newborns born by CD more frequently required postnatal clinical monitoring or admission to a neonatal intensive care unit. Conclusions: After 3‐minute DCC, the acid–base status shifted towards mixed acidosis in CDs and prevalent metabolic acidosis in VDs. CDs were associated with a more pronounced increase in arterial lactate, compared with VDs. Tweetable abstract: By 3‐minute DCC, acid–base status shifts towards mixed and metabolic acidosis in caesarean and vaginal delivery, respectively. Tweetable abstract: By 3‐minute DCC, acid–base status shifts towards mixed and metabolic acidosis in caesarean and vaginal delivery, respectively.